Factors influencing the organizational commitment of lecturers at non-public universities in Hanoi - Thuy, Nguyen Thi; Tu, Dương Minh (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze the factors influencing the organizational commitment of full-time lecturers at non-public universities in Hanoi, Vietnam. A survey was conducted with 356 full-time lecturers from 20 non-public universities in Hanoi. The data were analyzed using the PLS-SEM path model. The results indicate that all five factors studied (career development prospects, institutional brand, working environment, leadership style, and compensation and benefits) have a positive relationship with lecturers’ organizational commitment. Notably, career development prospects and institutional brand play a significant role in promoting faculty commitment. The study also suggests that income is not the most decisive factor in faculty commitment in this context.